The relationship between growth and pattern formation. Issue 2 (April 2016) - Bryant, Susan V.; Gardiner, David M.
Abstract: Successful development depends on the creation of spatial gradients of transcription factors within developing fields, and images of graded distributions of gene products populate the pages of developmental biology journals. Therefore the challenge is to understand how the graded levels of intracellular transcription factors are generated across fields of cells. We propose that transcription factor gradients are generated as a result of an underlying gradient of cell cycle lengths. Very long cell cycles will permit accumulation of a high level of a gene product encoded by a large transcription unit, whereas shorter cell cycles will permit progressively fewer transcripts to be completed due to gating of transcription by the cell cycle. We also propose that the gradients of cell cycle lengths are generated by gradients of extracellular morphogens/growth factors. The model of cell cycle gated transcriptional regulation brings focus back to the functional role of morphogens as cell cycle regulators, and proposes a specific and testable mechanism by which morphogens, in their roles as growth factors (how they were originally discovered), also determine cell fate.